Identification of a 48 kDa tubulin or tubulin-like C6/36 mosquito cells protein that binds dengue virus 2 using mass spectrometry - Chee, H.Y.; AbuBakar, Sazaly (2004)
Binding of dengue virus 2 (DENV-2) to C6/36 mosquito cells protein was investigated. A 48 kDa DENV-2-binding C6/36 cells protein (D2BP) was detected in a virus overlay protein-binding assay. The binding occurred only to the C6/36 cells cytosolic protein fraction and it was inhibited by free D2BP. D2BP was shown to bind to DENV-2 E in the far-Western-binding studies and using mass spectrometry (MS) and MS/MS, peptide masses of the D2BP that matched to beta-tubulin and alpha-tubulin chains were identified. These findings suggest that DENV-2 through DENV-2 E binds directly to a 48 kDa tubulin or tubulin-like protein of C6/36 mosquito cells. (C) 2004 Elsevier Inc. All rights reserved.